Wear-resistant and durable self-cleaning coating liquid for photovoltaic glass surface as well as preparation method and application of wear-resistant and durable self-cleaning coating liquid

By applying a specific wear-resistant and durable self-cleaning coating liquid on the surface of the photovoltaic glass, the problem of difficult to take into account both the self-cleaning and the permeability of the existing photovoltaic glass is solved, and high light transmittance, good self-cleaning and wear-resistant durability are achieved.

CN119875508APending Publication Date: 2025-04-25BEIJING GREEN ATU TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510101945.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

While existing photovoltaic glasses have self-cleaning properties, they are difficult to have good permeability and durability, and are susceptible to ultraviolet rays, temperature changes and chemical corrosion.

Method used

A wear-resistant and durable self-cleaning coating liquid is adopted, and the specific composition includes organopolysilazane resin, composite materials, hydrophobic silane, wear-resistant and anti-fouling agent. Through specific ratios and process preparation methods, a tough, durable and self-cleaning coating on the surface of the photovoltaic glass is formed.

Benefits of technology

It achieves high light transmittance of photovoltaic glass, significantly improves self-cleaning properties and wear-resistant durability, and can maintain the cleanliness and transparency of the glass in harsh environments and extend its service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005254413960000041
    Figure BDA0005254413960000041
  • Figure BDA0005254413960000051
    Figure BDA0005254413960000051
  • Figure BDA0005254413960000071
    Figure BDA0005254413960000071
Patent Text Reader

Abstract

The invention relates to the technical field of photovoltaic glass materials, and particularly discloses a wear-resistant and durable self-cleaning coating liquid for the surface of photovoltaic glass as well as a preparation method and application of the wear-resistant and durable self-cleaning coating liquid. The invention provides a wear-resistant and durable self-cleaning coating liquid for a photovoltaic glass surface. The coating liquid is prepared from 15-30 parts of organic polysilazane resin, 3-6 parts of a composite sizing material, 1-2 parts of hydrophobic silane, 1-2 parts of a wear-resistant agent, 0.1-0.4 part of an anti-fouling agent and 40-70 parts of a solvent, the preparation method of the composite rubber material comprises the following steps: mixing polyvinyl acetate homopolymer rubber powder, an acrylic anhydride / adipic acid / dipropylene glycol terpolymer and a titanate coupling agent, and carrying out a thermal reaction to obtain the composite rubber material. The wear-resistant agent is formed by mixing 10-30nm silicon dioxide, 50-80nm silicon dioxide and silicone powder. The photovoltaic glass with relatively high light transmittance can be obtained by utilizing the coating liquid disclosed by the invention, and meanwhile, the self-cleaning property, wear resistance and durability of the photovoltaic glass are obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of coating liquids, and in particular to a wear-resistant and durable self-cleaning coating liquid for photovoltaic glass surfaces, and a preparation method and application thereof. Background Art

[0002] With the increasing attention paid to renewable energy around the world, the photovoltaic industry has developed rapidly. As an important component of photovoltaic modules, the performance of photovoltaic glass directly affects the power generation efficiency of photovoltaic modules. Therefore, research and development of high-performance photovoltaic glass is of great significance to improving the overall efficiency of the photovoltaic industry.

[0003] Photovoltaic glass is not only required to have light transmittance, but also to have self-cleaning function. On the one hand, in order to improve the transmittance of photovoltaic glass to sunlight and increase the light energy utilization efficiency of photovoltaic power generation system, some studies have formed an anti-reflection film layer on the surface of photovoltaic glass; on the other hand, in order to make photovoltaic glass have good anti-fouling performance, some studies have formed a coating with self-cleaning function on the surface of photovoltaic glass. However, photovoltaic glass in the prior art has good self-cleaning property but it is difficult to have good anti-reflection property.

[0004] In addition, when studying the anti-reflection film layer or self-cleaning functional film layer formed on the surface of photovoltaic glass, it was found that this film layer would be gradually affected by factors such as ultraviolet rays, temperature changes, and chemical corrosion, resulting in poor durability and stability. Summary of the invention

[0005] In order to solve the above technical problems, the present application provides a wear-resistant and durable self-cleaning coating liquid for photovoltaic glass surface, and a preparation method and application thereof.

[0006] In the first aspect, the present application provides a wear-resistant and durable self-cleaning coating liquid for photovoltaic glass surface, characterized in that it specifically comprises the following components in parts by weight: 15-30 parts of organic polysilazane resin, 3-6 parts of composite rubber, 1-2 parts of hydrophobic silane, 1-2 parts of wear-resistant agent, 0.1-0.4 parts of antifouling agent, and 40-70 parts of solvent; The preparation method of the composite rubber material is as follows: after mixing polyvinyl acetate homopolymer rubber powder, acrylic anhydride / adipic acid / dipropylene glycol terpolymer and titanate coupling agent in a weight ratio of 30-40:5-15:0.5-1.5, heat-insulating and reacting at a temperature of 60-70° C. for 6-10 hours to obtain the composite rubber material; The anti-wear agent is composed of a mixture of 10-30nm silicon dioxide, 50-80nm silicon dioxide and silicone powder in a weight ratio of 0.5-1.5:2-4:5-13.

[0007] In the technical solution provided by the present application, the organic polysilazane resin provides excellent wear resistance for the glass with its unique structure and properties; this resin can form a tough coating on the surface of the glass, effectively resisting external friction and wear, thereby extending the service life of the glass; at the same time, its excellent chemical corrosion resistance can also protect the glass from corrosion by various chemicals. Secondly, the introduction of hydrophobic silane further enhances the self-cleaning function of the glass; this silane can form a hydrophobic film on the surface of the glass, making it difficult for water droplets to adhere to the surface of the glass, so that it can easily slide off and take away stains and dust on the surface; this self-cleaning effect not only reduces the frequency and difficulty of cleaning the glass, but also keeps the glass clean and transparent in various harsh environments.

[0008] The addition of polyvinyl acetate homopolymer powder in the composite rubber can enhance the wear resistance of glass; its unique adhesiveness and film-forming properties enable a solid protective film to be formed on the glass surface, effectively resisting external friction and wear, thereby extending the service life of the glass. The introduction of acrylic anhydride / adipic acid / dipropylene glycol terpolymer improves the durability of glass; this copolymer has excellent weather resistance and UV resistance, can resist the erosion of glass by harsh environments, and ensures that the glass maintains stable performance during long-term use. In addition, the addition of titanate coupling agent gives the glass a self-cleaning function; a special surface structure is formed in the composite rubber, making the glass hydrophobic and anti-fouling; rainwater or water droplets can easily slide off and take away stains and dust on the surface, keeping the glass clean and transparent. The composite rubber obtained by the heat preservation reaction under specific conditions can give the glass multiple functions of wear resistance, durability and self-cleaning.

[0009] The wear-resistant agent is composed of a mixture of 10-30nm silica, 50-80nm silica and silicone powder. Silica particles of different particle sizes can form a multi-level protective structure on the glass surface; small-sized 10-30nm silica particles can fill into microscopic depressions and gaps to enhance the surface smoothness of the glass, while large-sized 50-80nm silica particles can form a hard protective layer on the surface to effectively resist external friction and wear. Secondly, the addition of silicone powder further improves the durability and self-cleaning ability of the glass; silicone powder can form a waterproof and anti-fouling coating on the glass surface, making the glass more weather-resistant and anti-fouling; at the same time, silicone powder can also reduce the friction coefficient of the glass surface, reduce wear, and thus extend the service life of the glass. Therefore, this wear-resistant agent composed of a mixture of silica and silicone powder of different particle sizes can significantly improve the wear resistance, durability and self-cleaning ability of the glass.

[0010] Preferably, the wear-resistant and durable self-cleaning coating liquid for the surface of photovoltaic glass specifically comprises the following components in parts by weight: 18-26 parts of organic polysilazane resin, 4-5 parts of composite rubber, 1.2-1.8 parts of hydrophobic silane, 1.2-1.8 parts of wear-resistant agent, 0.2-0.3 parts of anti-fouling agent, and 50-60 parts of solvent.

[0011] Preferably, the preparation method of the composite rubber material is: after mixing polyvinyl acetate homopolymer powder, acrylic anhydride / adipic acid / dipropylene glycol terpolymer and titanate coupling agent in a weight ratio of 32-38:7-12:0.8-1.2, heat-retaining reaction at a temperature of 60-70°C for 7-9 hours to obtain the composite rubber material.

[0012] Preferably, in the composite rubber material, the preparation method of the acrylic anhydride / adipic acid / dipropylene glycol terpolymer is: fully and evenly mix acrylic anhydride and dicumyl peroxide, then add adipic acid and dipropylene glycol, react for 60-90 minutes at room temperature, and then extrude at 220-240°C to obtain; the weight ratio of acrylic anhydride, dicumyl peroxide, adipic acid and dipropylene glycol is 10:0.05-0.15:1-2:5-7.

[0013] Preferably, the organic polysilazane resin is selected from one or more of polymethylsilazane resin and polyvinylsilazane resin.

[0014] Preferably, the hydrophobic silane is selected from one or more of aminopropyltriethoxysilane, propyltrimethoxysilane and polydimethylsiloxane.

[0015] Preferably, the antifouling agent is composed of a mixture of N-phenyl-N′-isopropyl-p-phenylenediamine, TEGO5000N and zinc sulfate in a weight ratio of 8-12:1-3:0.8-1.4.

[0016] After experimental analysis, the applicant found that the use of raw materials in the above weight ratio as anti-fouling agents can further improve the comprehensive application performance of photovoltaic glass. N-phenyl-N′-isopropyl-p-phenylenediamine in the anti-fouling agent is an effective antioxidant that can enhance the durability of glass; its unique chemical structure can effectively resist ultraviolet rays and chemical corrosion, protect the glass from damage by the external environment, and thus extend the service life of the glass. The introduction of TEGO5000N further enhances the self-cleaning and anti-fouling capabilities of the glass; it can form a layer of microscopic hydrophobic structure on the surface of the glass, making it difficult for water droplets and stains to adhere. The addition of zinc sulfate provides additional wear resistance to the glass. Zinc ions can combine with the silicon-oxygen bonds on the surface of the glass to enhance the hardness and wear resistance of the glass, making it more resistant to daily friction and wear.

[0017] In summary, this anti-fouling agent composed of a mixture of N-phenyl-N′-isopropyl-p-phenylenediamine, TEGO5000N and zinc sulfate can significantly improve the wear resistance, durability and self-cleaning ability of glass.

[0018] Preferably, the solvent is composed of a mixture of n-hexanol and N,N-dimethylacetamide in a weight ratio of 3-5:0.8-1.2.

[0019] In the second aspect, the present application provides a method for preparing the above-mentioned wear-resistant and durable self-cleaning coating liquid for the surface of photovoltaic glass, which is characterized in that it specifically includes the following steps in sequence: weighing each component raw material, adding the organic polysilazane resin and the composite rubber to the solvent, stirring at 400-600r / min for 5-15min on a high-speed stirrer to mix evenly, and then continuing to add hydrophobic silane, wear-resistant agent, and anti-fouling agent, adjusting the speed to 800-1200r / min and continuing to stir for 30-60min to obtain the self-cleaning coating liquid for the surface of photovoltaic glass.

[0020] In a third aspect, the present application provides the use of the above-mentioned wear-resistant and durable self-cleaning coating liquid for the surface of photovoltaic glass in the preparation of photovoltaic glass materials.

[0021] In summary, the technical solution of this application has the following effects: The wear-resistant and durable self-cleaning coating liquid prepared in the present application is used to prepare wear-resistant and durable self-cleaning photovoltaic glass, which can obtain photovoltaic glass with high light transmittance, and at the same time significantly improve the self-cleaning and wear-resistant durability of the photovoltaic glass.

[0022] The present application further improves the application performance of the wear-resistant and durable self-cleaning coating liquid in the preparation of photovoltaic glass materials by optimizing and matching the dosage of each component and simultaneously screening the types of composite rubber, wear-resistant agent and anti-fouling agent. DETAILED DESCRIPTION

[0023] The present application is further described in detail below in conjunction with examples, comparative examples and performance testing experiments. These examples should not be construed as limiting the scope of protection claimed in the present application.

[0024] Polyvinyl silazane resin (DURAZNE 1800) was purchased from Merck, Germany; silicone powder (model KJSI660) was purchased from Dongguan Kangjin New Material Technology Co., Ltd.; polyvinyl acetate homopolymer rubber powder (DY5010 latex powder) and ethylene / vinyl acetate copolymer rubber powder (DY5030 rubber powder) were purchased from Guangzhou Yuanye Industrial Co., Ltd. Example

[0025] Examples 1-5 Examples 1-5 respectively provide a wear-resistant and durable self-cleaning coating liquid for the surface of photovoltaic glass.

[0026] The difference between the above embodiments is that the dosage of each component in the wear-resistant and durable self-cleaning coating liquid for the surface of photovoltaic glass is different, as shown in Table 1.

[0027] The preparation method of the wear-resistant and durable self-cleaning coating liquid for the photovoltaic glass surface in the above embodiment is: (1) The preparation method of acrylic anhydride / adipic acid / dipropylene glycol terpolymer is as follows: 10 g of acrylic anhydride and 0.1 g of dicumyl peroxide are fully mixed, and then 1.5 g of adipic acid and 6 g of dipropylene glycol are added, and the mixture is reacted at room temperature for 75 minutes, and then extruded at 230° C. to obtain the terpolymer; the weight ratio of acrylic anhydride, dicumyl peroxide, adipic acid, and dipropylene glycol is 10:0.1:1.5:6.

[0028] The preparation method of the composite rubber is as follows: a mixture of 35 g of polyvinyl acetate homopolymer powder, 10 g of acrylic anhydride / adipic acid / dipropylene glycol terpolymer and 1 g of isopropyl tri(dioctyl pyrophosphate) titanate coupling agent in a weight ratio of 35:10:1 is treated by heat preservation and activation at 65°C in a water bath for 8 hours to obtain the composite rubber.

[0029] (2) According to Table 1, weigh the corresponding weights of the components; Weigh the raw materials of each component, add polyvinyl silazane resin and composite rubber into the solvent (composed of a mixture of n-hexanol and N,N-dimethylacetamide in a weight ratio of 4:1), stir on a high-speed stirrer at 500 r / min for 10 min to mix evenly, then continue to add aminopropyl triethoxysilane, wear-resistant agent (the wear-resistant agent is composed of a mixture of 10-30nm silica, 50-80nm silica and silicone powder in a weight ratio of 1:3:9), anti-fouling agent (composed of a mixture of N-phenyl-N′-isopropyl-p-phenylenediamine, TEGO5000N and zinc sulfate in a weight ratio of 10:2:1.1), adjust the speed to 1000 r / min and continue stirring for 45 min to obtain: self-cleaning coating liquid for photovoltaic glass surface.

[0030] Table 1 Amount of each component in the wear-resistant and durable self-cleaning coating liquid in Examples 1-5 and Comparative Examples 1-2 Embodiment 6-9 Examples 6-9 respectively provide a wear-resistant and durable self-cleaning coating liquid for the surface of photovoltaic glass.

[0031] The differences between the above embodiment and embodiment 3 are as follows: the preparation method of the composite rubber is different, specifically: in embodiment 6: a mixture of 35g of polyvinyl acetate homopolymer powder, 10g of acrylic anhydride / adipic acid / dipropylene glycol terpolymer and 1g of isopropyl tri(dioctyl pyrophosphate) titanate coupling agent in a weight ratio of 30:15:1.5 is treated by heat preservation and activation at 65°C in a water bath for 8h to obtain the composite rubber.

[0032] In Example 7: A mixture of 35 g of polyvinyl acetate homopolymer powder, 10 g of acrylic anhydride / adipic acid / dipropylene glycol terpolymer and 1 g of isopropyl tri(dioctyl pyrophosphate) titanate coupling agent in a weight ratio of 40:5:0.5 was activated in a water bath at 65°C for 8 hours to obtain a polymer.

[0033] In Example 8: A mixture of 35 g of polyvinyl acetate homopolymer powder, 10 g of acrylic anhydride / adipic acid / dipropylene glycol terpolymer and 1 g of isopropyl tri(dioctyl pyrophosphate) titanate coupling agent in a weight ratio of 32:12:1.2 was activated in a water bath at 65°C for 8 hours to obtain a polymer.

[0034] In Example 9: A mixture of 35 g of polyvinyl acetate homopolymer powder, 10 g of acrylic anhydride / adipic acid / dipropylene glycol terpolymer and 1 g of isopropyl tri(dioctyl pyrophosphate) titanate coupling agent in a weight ratio of 48:7:0.8 was activated in a water bath at 65°C for 8 hours to obtain a polymer.

[0035] The other process parameters in the above embodiment are the same as those in embodiment 3.

[0036] Examples 10-13 Examples 10-13 respectively provide a wear-resistant and durable self-cleaning coating liquid for the surface of photovoltaic glass.

[0037] The difference between the above embodiment and embodiment 3 is that the types of anti-wear agents are different, as shown below.

[0038] In Example 10: the wear-resistant agent is composed of a mixture of 10-30nm silicon dioxide, 50-80nm silicon dioxide and silicone powder in a weight ratio of 0.5:4:13.

[0039] In Example 11: the wear-resistant agent is composed of a mixture of 10-30nm silicon dioxide, 50-80nm silicon dioxide and silicone powder in a weight ratio of 1.5:2:5.

[0040] In Example 12: the wear-resistant agent is composed of a mixture of 10-30nm silicon dioxide, 50-80nm silicon dioxide and silicone powder in a weight ratio of 0.8:3.5:11.

[0041] In Example 13: the wear-resistant agent is composed of a mixture of 10-30nm silicon dioxide, 50-80nm silicon dioxide and silicone powder in a weight ratio of 1.2:2.5:7.

[0042] The other process parameters in the above embodiment are the same as those in embodiment 3.

[0043] Examples 14-17 Examples 14-17 respectively provide a wear-resistant and durable self-cleaning coating liquid for the surface of photovoltaic glass.

[0044] The difference between the above embodiment and embodiment 3 is that the types of antifouling agents are different, as shown below.

[0045] In Example 14: the antifouling agent is composed of a mixture of N-phenyl-N′-isopropyl-p-phenylenediamine, TEGO5000N and zinc sulfate in a weight ratio of 10:2:1.1.

[0046] In Example 15, the antifouling agent is composed of a mixture of N-phenyl-N′-isopropyl-p-phenylenediamine, TEGO5000N and zinc sulfate in a weight ratio of 14:0.5:2.

[0047] In Example 16, the antifouling agent is composed of a mixture of N-phenyl-N′-isopropyl-p-phenylenediamine, TEGO5000N and zinc sulfate in a weight ratio of 8:3:1.5.

[0048] In Example 17: the antifouling agent is composed of a mixture of N-phenyl-N′-isopropyl-p-phenylenediamine, TEGO5000N and zinc sulfate in a weight ratio of 12:1:0.8.

[0049] The other process parameters in the above embodiment are the same as those in embodiment 3.

[0050] Comparative Example Comparative Example 1-2 Comparative Examples 1-2 respectively provide a wear-resistant and durable self-cleaning coating liquid for the surface of photovoltaic glass.

[0051] The difference between the comparative example and Example 3 is that the dosage of each component in the wear-resistant and durable self-cleaning coating liquid for the surface of photovoltaic glass is different, as shown in Table 1.

[0052] The other process parameters in the above comparative example are the same as those in Example 3.

[0053] Comparative Examples 3-4 Comparative Examples 3-4 respectively provide a wear-resistant and durable self-cleaning coating liquid for the surface of photovoltaic glass.

[0054] The differences between the above comparative example and Example 3 are specifically as follows.

[0055] In Comparative Example 3: The preparation method of the composite rubber material is as follows: a mixture of 35 g of ethylene / vinyl acetate copolymer rubber powder, 10 g of acrylic anhydride / adipic acid / dipropylene glycol terpolymer and 1 g of isopropyl tri(dioctyl pyrophosphate) titanate coupling agent in a weight ratio of 35:10:1 is treated by heat preservation and activation at 65°C in a water bath for 8 hours to obtain the composite rubber material.

[0056] In Comparative Example 4: the wear-resistant agent is composed of a mixture of 10-30 nm silicon dioxide, 50-80 nm silicon dioxide and silicone powder in a weight ratio of 2:1:1.

[0057] The other process parameters in the above comparative example are the same as those in Example 3.

[0058] Performance testing Take photovoltaic glass, clean it, blow dry it with nitrogen, and then coat the surface with the wear-resistant and durable self-cleaning coating liquid prepared in the embodiment or comparative example, with a single-side coating amount of 35g / m 2 ; vacuum drying at 70°C for 30 min, then vacuum drying at 130°C for 75 min, and then curing with ultraviolet light to obtain the product.

[0059] (1) Light transmittance: The transmittance of the coated photovoltaic glass at 600 nm was tested using a UV-3600 spectrophotometer.

[0060] (2) Water contact angle test: The droplet size during the test was 2 μL, and a water contact angle tester was used to test the water contact angle of the coated photovoltaic glass surface.

[0061] (3) Abrasion resistance test: Abrasion resistance test was conducted using an abrasion tester. The reciprocating test method was used. A 1kg weight was pressed on a scouring pad dipped in alcohol to perform a plane reciprocating motion on the sample for friction test. After 10,000 frictions, a light transmittance test was performed. Abrasion resistance = light transmittance after the test / light transmittance before the test × 100%.

[0062] (4) Humidity and frost resistance: Tested in accordance with JC / T 2170-2013 / 6.11 standard, test conditions: relative humidity 85% ± 5%, maximum temperature 85℃ ± 2℃ dropped to -40℃ ± 2℃, number of cycles 20 times; test light transmittance after the test. Humidity and frost resistance = light transmittance after the test / light transmittance before the test × 100%.

[0063] (5) Moisture and heat resistance: Tested in accordance with JC / T 2170-2013 / 6.12, the test conditions are: relative temperature 85% ± 2%, relative humidity 85% ± 2%, test time is 2000 hours; test the light transmittance after the test. Moisture and heat resistance = light transmittance after the test / light transmittance before the test × 100%.

[0064] Test results: as shown in Table 2.

[0065] Table 2 Application performance of wear-resistant and durable self-cleaning coating liquid for photovoltaic glass surface in Examples and Comparative Examples Combined with the test results in Table 2, it can be seen that the wear-resistant, durable self-cleaning coating liquid for the surface of photovoltaic glass prepared by the technical solution of the present application can obtain a wear-resistant, durable, self-cleaning photovoltaic glass with a high light transmittance, which can significantly improve the self-cleaning property of the photovoltaic glass; at the same time, the wear-resistant, durable, self-cleaning photovoltaic glass prepared by the present application has a high light transmittance retention rate after wear resistance test, wet frost test, and wet heat test; that is, it indicates that the photovoltaic glass has excellent wear resistance and durability.

[0066] By comparing the test results of Examples 1-5 with those of Comparative Examples 1-2, it can be seen that the amount of each component in the wear-resistant and durable self-cleaning coating liquid used for the surface of photovoltaic glass has a great influence on the performance of the glass. The present application can obtain photovoltaic glass with excellent comprehensive performance by reasonably controlling the dosage ratio of each component.

[0067] By comparing the test results of Examples 3, 6-9 with those of Comparative Example 3, it can be seen that the present application utilizes polyvinyl acetate homopolymer powder, acrylic anhydride / adipic acid / dipropylene glycol terpolymer and titanate coupling agent in a weight ratio of 30-40:5-15:0.5-1.5 to prepare a composite rubber as a raw material component for a wear-resistant and durable self-cleaning coating liquid for the surface of photovoltaic glass, thereby further improving the performance of the photovoltaic glass.

[0068] By comparing the test results of Examples 3 and 10-13, it can be seen that the present application utilizes a mixture of 10-30nm silica, 50-80nm silica and silicone powder in a weight ratio of 0.5-1.5:2-4:5-13 to form an anti-wear agent, which further improves the performance of photovoltaic glass.

[0069] By comparing the test results of Examples 3 and 14-17, it can be seen that the present application uses a mixture of N-phenyl-N′-isopropyl-p-phenylenediamine, TEGO5000N and zinc sulfate in a weight ratio of 8-12: 1-3: 0.8-1.4 to form an anti-fouling agent, which further improves the performance of photovoltaic glass.

[0070] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.

Claims

1. A wear-resistant and durable self-cleaning coating liquid for photovoltaic glass surface, characterized in that: Specifically, it includes the following components in parts by weight: 15-30 parts of organic polysilazane resin, 3-6 parts of composite rubber, 1-2 parts of hydrophobic silane, 1-2 parts of wear-resistant agent, 0.1-0.4 parts of antifouling agent, and 40-70 parts of solvent; The preparation method of the composite rubber material is as follows: after mixing polyvinyl acetate homopolymer rubber powder, acrylic anhydride / adipic acid / dipropylene glycol terpolymer and titanate coupling agent in a weight ratio of 30-40:5-15:0.5-1.5, heat-insulating and reacting at a temperature of 60-70° C. for 6-10 hours to obtain the composite rubber material; The wear-resistant agent is composed of a mixture of 10-30nm silicon dioxide, 50-80nm silicon dioxide and silicone powder in a weight ratio of 0.5-1.5:2-4:5-13.

2. The wear-resistant and durable self-cleaning coating liquid for photovoltaic glass surface according to claim 1, characterized in that: Specifically, the composition comprises the following components in parts by weight: 18-26 parts of organic polysilazane resin, 4-5 parts of composite rubber, 1.2-1.8 parts of hydrophobic silane, 1.2-1.8 parts of anti-wear agent, 0.2-0.3 parts of anti-fouling agent and 50-60 parts of solvent.

3. The wear-resistant and durable self-cleaning coating liquid for photovoltaic glass surface according to claim 1, characterized in that: The preparation method of the composite rubber material is as follows: after mixing polyvinyl acetate homopolymer rubber powder, acrylic anhydride / adipic acid / dipropylene glycol terpolymer and titanate coupling agent in a weight ratio of 32-38:7-12:0.8-1.2, heat-insulating and reacting at a temperature of 60-70° C. for 7-9 hours to obtain the composite rubber material.

4. The wear-resistant and durable self-cleaning coating liquid for photovoltaic glass surface according to claim 1, characterized in that: In the composite rubber material, the preparation method of the acrylic anhydride / adipic acid / dipropylene glycol terpolymer is as follows: acrylic anhydride and dicumyl peroxide are fully mixed, then adipic acid and dipropylene glycol are added, reacted at room temperature for 60-90 minutes, and then extruded at 220-240° C. to obtain the terpolymer; the weight ratio of acrylic anhydride, dicumyl peroxide, adipic acid and dipropylene glycol is 10: 0.05-0.15:1-2:5-7。 5. The wear-resistant and durable self-cleaning coating liquid for photovoltaic glass surface according to claim 1, characterized in that: The organic polysilazane resin is selected from one or more of polymethylsilazane resin and polyvinylsilazane resin.

6. The wear-resistant and durable self-cleaning coating liquid for photovoltaic glass surface according to claim 1, characterized in that: The hydrophobic silane is selected from one or more of aminopropyltriethoxysilane, propyltrimethoxysilane and polydimethylsiloxane.

7. The wear-resistant and durable self-cleaning coating liquid for photovoltaic glass surface according to claim 1, characterized in that: The antifouling agent is composed of N-phenyl-N'-isopropyl p-phenylenediamine, TEGO5000N and zinc sulfate in a weight ratio of 8-12:1-3:0.8-1.

4.

8. The wear-resistant and durable self-cleaning coating liquid for photovoltaic glass surface according to claim 1, characterized in that: The solvent is composed of 3-5 weight ratio: It is composed of a mixture of 0.8-1.2 n-hexanol and N,N-dimethylacetamide.

9. The method for preparing the wear-resistant and durable self-cleaning coating liquid for photovoltaic glass surface according to any one of claims 1 to 8, characterized in that: Specifically, the process includes the following steps: weighing each component raw material, adding the organic polysilazane resin and the composite rubber into the solvent, stirring at 400-600 r / min for 5-15 min on a high-speed stirrer to mix evenly, then adding hydrophobic silane, wear-resistant agent and anti-fouling agent, adjusting the rotation speed to 800-1200 r / min and continuing stirring for 30-60 min to obtain the self-cleaning coating liquid for the surface of photovoltaic glass.

10. Use of the wear-resistant and durable self-cleaning coating liquid for photovoltaic glass surface according to any one of claims 1 to 8 in the preparation of photovoltaic glass materials.